Assessment of root canal configuration of mandibular incisors using cone-beam computed tomography in a sample of Iraqi patient - Saud Jasim Othman Dizayee; Raid Fahim Selman (Advanced Medical Journal)
Background and objectives: Mandibular incisors mostly have 1 root canal. The purpose of this study was to investigate the prevalence of root canals configurations in mandibular incisors and to investigate the gender prevalence.